LEGAL PROTECTION OF OCCUPATIONAL SAFETY AND HEALTH FOR PHARMACISTS OF CLINICS IN SEMARANG - Saputri, Heni; Absori; Rizka (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
Every worker has the rights to receive occupational health and safety guarantees. Occupational safety and health are not only a worker's rights, but it is also the employer's responsibility to provide. Protection of norms for pharmaceutical workers, who are included in the group of health workers, includes wages, working time, rest time, and leave. Meanwhile, norms of social security for workers who manage the clinic by ensuring participation in the national health insurance (JKN) are held through the JKN-BPJS Health program and work accident insurance and death benefits are held through the BPJS employment program. In practice, employers have not made this a priority that must be received by every employee. This is felt by several pharmacists at clinics in Semarang. Based on the problems above, it is necessary to conduct the research about the legal protection of occupational safety and health for pharmacists at clinics in Semarang Regency. Research Objectives to optimize the implementation of occupational safety and health legal protection for pharmacy staff at clinics in Semarang. This study used a descriptive method with a qualitative approach and a case study design. The Implementation of Occupational Safety and Health Legal Protection for Pharmacy Personnel at Clinics in Semarang Regency has not been carried out in accordance with the applicable laws and regulations. There are some clinics do not have complete personal protective equipment (PPE) according to standards, and the rights to health and safety that should be given by employers. the pharmacist clinics is not guaranteed yet. Occupational safety and health legal protection for pharmacists at clinics in Semarang has not been implemented in accordance with the applicable laws and regulations.